A MERN based Web Application for Analysing Student Dropout - R., Sathyabama A; R., Karthikeyan; K., Sreeram (Journal of Trends in Computer Science and Smart Technology, 2024)
The technological advancement has led to the rapid changes in education system, enhancing the student’s engagement and improving personalized education. However, one major challenge that is faced by the school is students leaving before completing their courses. The proposed system aims to address this issue by identifying the various factors that lead to the student dropouts. The user-friendly website developed in the proposed work allows both students and educational institutions to provide the reasons for student dropouts. The system is designed to analyse the collected data, extract valuable information, and identify hidden patterns. These insights are then presented as visuals, such as charts and graphs, to help better understand the underlying causes of dropouts. The primary objective of the proposed system, developed using MERN, is to create a more inclusive and supportive learning environment that focuses on both student academic achievement and safety. Ultimately, this system aims to reduce dropout rates and improve access to quality education for all students, regardless of their background or circumstances.
Keywords: Student Dropout; MERN; Data Analysis; Dropout Prevention; Education System